The value of newly created wood pastures for bird and grasshopper conservation. (September 2019) - Rösch, Verena; Hoffmann, Malte; Diehl, Ulrich; Entling, Martin H.
Abstract: Modern production forests in Europe have closed canopies. As a consequence, the biodiversity associated with open woodland is declining. Forest grazing that created open conditions was once widespread. It was largely abandoned during the 20th century but is currently receiving increasing attention as a tool in nature conservation. In order to elucidate the value of newly created wood pastures for the conservation of birds and grasshoppers we selected nine wood pastures (WP) in southern Rhineland-Palatinate (Germany). In most of them part of the trees had been removed to create more open conditions. We selected adjacent ungrazed forests (F) and open pastures (OP) for comparison. Birds were recorded via territory mapping, grasshoppers via standardised transect surveys. We found higher bird species richness in WP compared to F and OP and more breeding pairs per area compared to open pastures. Target species for conservation like European nightjar ( Caprimulgus europaeus ) were only recorded in WP. Grasshopper species richness in WP and OP was similar but low in F. Species with conservation relevance only occurred in WP and OP. Community composition of both taxa differed between habitat types and β-diversity of birds was significantly higher among WP than among F and OP. We conclude that even in recently established sites, canopy opening in connection with grazing is a very effective tool in nature conservation, especially in order to promote species that favour open, structurally diverse forest habitats. Highlights: Forest grazing is increasingly used for nature conservation. New wood pastures quickly develop distinct bird and grasshopper communities. Wood pastures and pastures had higher conservation value than forests. Wood pastures are a valuable addition to pastures and ungrazed forest.